Evaluation of T Cell Response to SARS-CoV-2 in Kidney Transplant Recipients Receiving Monoclonal Antibody Prophylaxis and the Utility of a Bivalent mRNA Vaccine Booster Dose - Dominique Bertrand; Charlotte Laurent; Mathilde Lemoine; Ludivine Lebourg; Mélanie Hanoy; Frank Le Roy; Dorian Nezam; Diana Pruteanu; Steven Grange; Tristan De Nattes; Véronique Lemée; Dominique Guerrot; et al. (Microorganisms, 2024)
Monoclonal antibodies have been administered to kidney transplant recipients (KTRs) with a poor or non-responder status to SARS-CoV-2 vaccination. The cellular response to SARS-CoV-2 has been poorly studied in this context. We assessed the T cell response to SARS-CoV-2 in 97 patients on the day of the injection of tixagevimab/cilgavimab using an IFNγ enzyme-linked immunospot assay (ELISPOT). Among the 97 patients, 34 (35%) developed COVID-19 before the injection. Twenty-nine (85.3%) had an ELISPOT compatible with a SARS-CoV-2 infection. There was no difference between KTRs under belatacept or tacrolimus treatment. Sixty-three patients (64.9%) had no known COVID-19 prior to the ELISPOT, but nine (14.3%) had a positive ELISPOT. In 21 KTRs with a positive ELISPOT who received a booster dose of a bivalent mRNA vaccine, median antibody titers and spike-reactive T cells increased significantly in patients under tacrolimus but not belatacept. Our study emphasizes the potential usefulness of the exploration of immune cellular response to SARS-CoV-2 by ELISPOT. In KTRs with a positive ELISPOT and under CNI therapy, a booster dose of mRNA vaccine seems effective in inducing an immune response to SARS-CoV-2.